The Creative Problem Solving (CPS) Learning Model Effect on Students’ Mathematics Learning Results at Junior High Schools of Dumai City - Abdurrahman; Sindi Amelia; Kiki Hartiwi (Mathematics Research and Education Journal, 2022)
This study aims to see the Creative Problem Solving (CPS) learning model's effect on the mathematics learning result of eighth-grade students of State Junior High School 21 (SJHS) Dumai. The quasi-experimental with a non-equivalent control group approach are proposed in this research. Purposive sampling was the correct technique to complete the study. To know which one was the best, two classes were used to compare the learning result. One type used CPS, and others used conventional learning. The data collection instrument was in the form of pretest and posttest questions. The data collection technique in this study was done by using a test technique. Data analysis were normality, homogeneity, t-test. The results showed an effect of CPS on the mathematics learning outcomes of the experimental and control class students. Results showed that a significant difference was acquired between CPS and conventional learning. This can be seen from t-count > t-table which is 4.47 > 1.67. Following the criteria, H0 is rejected, and H1 is accepted. The conclusion was a significant effect of the CPS learning model on the mathematics learning results of eighth-grade students of SJHS 21 Dumai